(untitled) (Nepalese Veterinary Journal, 2017)
An experiment was carried out to study the development of sequential histological lesions and efficacy of certain diagnostic tests in experimentally induced subclinical paratuberculosis infection in goats. Twelve goats of 8-12 weeks age were infected with 4.23 x 109 Mycobacterium avium subsp. Paratuberculosis on 8 occasions. Eight goats were kept as in-contact controls and 4 as uninfected controls. Diagnostic tests, gross and histopathological studies were carried out at 3, 6, 9 and 12 months post-infection. Two goats were positive in the AGID test at 12MPI. Three goats, one at 9 MPI and two at 12 MPI were positive in faecal culture. Tissue PCR detected one goat positive each at 9 and 12 MPI. Six (50%) of 12 infected goats had gross and histological lesions. Marked enlargements of the mesenteric lymph nodes were observed in the early stages (3 and 6 months post infection) of infection. Mucosal thickening and corrugation of the jejunal and ileal mucosae, enlargement and oedema of the mesenteric lymph nodes, dilatation of lymphatics and gelatinisation of mesenteric fat were observed in goats euthanised at 9 and 12 MPI. Histological lesions consisting of flat and broad villi with mild infiltration of lymphocytes and macrophages in the intestinal villi and crypts were common at 3 MPI and 6 MPI. Focal infiltration of macrophages in Peyer’s patches and giant cells were found in the mesenteric lymph nodes at 6 MPI. Broadened villi and increased infiltration of lymphocytes and macrophages with Langhan’s giant cells were observed in the villi and crypts at 9 MPI and 12 MPI goats. Acid-fast bacilli were detected in 3 goats, one each at 6, 9 and 12 MPI.